Konstruksi Hukum Pidana terhadap Peserta Arisan Online yang Tidak Memenuhi Kewajiban Pembayaran - Yoga Aditama (CV Rewang Rencang, 2025)
In Indonesia, arisan is a social phenomenon that occurs in various regions. Until now, arisan has become a community activity, for example in government agencies, companies, neighbourhood associations, schools, and even places of worship. places of worship. As a social activity, some people consider that arisan functions as a medium of attraction to visit each other, get to know each other, give and need each other, and as a medium of harmony. Protection legal protection for the parties in online arisan activities can still be carried out by referring to existing regulations, such as the Civil Code and the Civil Code. referring to existing regulations, such as the Civil Code and ITE Law. Argumentation The right argument to claim liability in this online arisan case lies in the fulfilment of the rights and obligations that have been fulfilled. lies in the fulfilment of agreed rights and obligations, as well as the application of sanctions in accordance with applicable legal provisions. application of sanctions in accordance with applicable legal provisions. This research is a normative research that studies the purpose of law, the values of justice, validity of legal rules, legal concepts, and legal norms. Source materials used in this research are primary legal materials, secondary legal materials and tertiary legal materials. and tertiary legal materials. Primary legal material is Indonesian Law. Furthermore, the data collected is analysed qualitatively. The arisan maker and arisan members have the responsibility to lend arisan money and receive a certain amount of deposit money from arisan members. The arisan members also have the responsibility to return the loan in the form of arisan deposit, with the same total deposit that was loaned in the initial agreement. Members are entitled to receive arisan money loans. The arisan maker and arisan members can be considered in default if they do not hand over the arisan money on schedule or if the loan amount does not match the schedule. The arisan creator can be sentenced to imprisonment if they embezzle the online arisan funds in accordance with Articles 372 and 378 of the Criminal Code on embezzlement and fraud. If they do not return the loan in its entirety or not according to the original amount or exceed the agreed time period, they are considered in default.